2002
DOI: 10.1024/0300-9831.72.5.315
|View full text |Cite
|
Sign up to set email alerts
|

Increased Lipid Peroxidation in Serum and Low-Density Lipoproteins Associated with Aging in Humans

Abstract: This study was carried out in 140 healthy subjects who were divided into three subgroups of age: young (21-40 years), mature (41-60 years), and elderly (61-85 years) to investigate lipid peroxides and the antioxidant system in serum and low-density lipoproteins (LDL). Serum levels of cholesterol and LDL-cholesterol increased with age. The elderly group was found to have higher polyunsaturated fatty acid (PUFA) levels, thiobarbituric acid reactive substances (TBARS), diene conjugates, and lower cholesterol-adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…In another study in Fischer-344 rats, total plasma PUFA percent composition increased with age (Engler et al 1998). In humans, total unesterified fatty acid concentrations increased with age (Bonadonna et al 1994), as did EPA and DHA concentrations in plasma total lipids (Balkan et al 2002;Fortier et al 2010). The inconsistency in study outcomes may relate to differences in DHA synthesis capacity between rodents and humans (Wang et al 2006), diet, or the fact that most studies measured n-3 PUFA concentrations in plasma total lipid instead of esterified and unesterified fractions (Engler et al 1998;Fortier et al 2010).…”
Section: Ementioning
confidence: 99%
“…In another study in Fischer-344 rats, total plasma PUFA percent composition increased with age (Engler et al 1998). In humans, total unesterified fatty acid concentrations increased with age (Bonadonna et al 1994), as did EPA and DHA concentrations in plasma total lipids (Balkan et al 2002;Fortier et al 2010). The inconsistency in study outcomes may relate to differences in DHA synthesis capacity between rodents and humans (Wang et al 2006), diet, or the fact that most studies measured n-3 PUFA concentrations in plasma total lipid instead of esterified and unesterified fractions (Engler et al 1998;Fortier et al 2010).…”
Section: Ementioning
confidence: 99%
“…In agreement with this theory, Balkan et al revealed that antioxidant activities in elderly subjects (61 to 85 years old) were lower than young people (32).…”
Section: Discussionmentioning
confidence: 51%
“…Nothing is known about an age-related effect on the studied parameters in this range of age. Increased plasma levels of lipid peroxides and Cu have manly been shown in elderly [65][66][67]. If there is a positive correlation between age and the variables measured, the effect we have seen might be underestimated.…”
Section: Discussionmentioning
confidence: 58%